CLASSIFICATION OF COMMODITY DERIVATIVES AS FINANCIAL INSTRUMENTS : Determining conceptual and contractual differences of commodity derivatives and spot transactions in the context of MiFID II (2014/65/EU) Annex 1 C5 – C7 - Mäki, Tiia (My University, 2020)
Since the early days, one the aims of the European Union have been to create a functional common market. The single market has been furthered by mix of legislative, administrative and judicial initiatives. In 1957, European Economic Community (EEC) created an obligation for Member States to abolish restrictions on capital movements, which was necessary for the functionality of the common market. Later all restrictions on the free movement of capital between Member States were prohibited. The development of the single market demands positive integration, which includes harmonization of national laws through EU directives. However, it is not obvious that the European Union always succeeds with the harmonization. This master thesis analyzes the definition of financial instrument in the context of MiFID II Annex 1 C5-C7. The research provides with insights in commodity derivative markets as well as proves the challenges in determining the instruments traded in the market. The focus of the study is on analyzing the functionality of the common market in this context, by comparing the interpretation of the relevant legislation in different Member States. The research also evaluates the possibilities to challenge incorrectly applied EU law by means provided by the European Union. Furthermore, this thesis suggests clarifications on the definitions provided in MiFID II Annex 1 C5-C7. The suggestions are reasoned based on comparison between commodity derivatives and spot transactions. The comparison focuses on analyzing the definitions provided in the legislation and corresponding guidelines by the authorities as well as the market practices. The conclusion of the research is that the definition of commodity derivative should be further clarified in order the aims of the common financial market to be reached.
Keywords: financial markets, Markets in Financial Instruments Directive, commodity derivatives, common financial market